2020
DOI: 10.3389/fgene.2020.00324
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison Between Plasma and Stool Methylated SEPT9 Tests for Detecting Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the most common type of malignancies of the gastrointestinal tract worldwide. Plasma methylated SEPT9 test has been used clinically for CRC screening for several years, but the study about the performance comparison between plasma and stool has rarely been reported. In this study, 124 plasma samples, 100 stool samples, and 60 sets of plasma and paired stool samples were collected and tested by a methylated SEPT9 test in three PCR replicates. The results indicated methylated SEPT9 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Therefore, it is conceivable that tumor DNA was more concentrated in stool than in plasma, resulting in a higher sensitivity for CRC detection with stool samples. Such a phenomenon was also observed for methylated SEPT9 and methylated SDC2 in our previous studies (50,56,57). When compared to other methylation biomarkers in stoolbased tests, the sensitivities of methylated C9orf50 and methylated KCNQ5 for all stage CRC detection, 85.9 and 77.3% respectively, fell within the range of other markers from 71.2% for methylated HPP1 (55) to 92.5% for methylated COL4A2 (33).…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, it is conceivable that tumor DNA was more concentrated in stool than in plasma, resulting in a higher sensitivity for CRC detection with stool samples. Such a phenomenon was also observed for methylated SEPT9 and methylated SDC2 in our previous studies (50,56,57). When compared to other methylation biomarkers in stoolbased tests, the sensitivities of methylated C9orf50 and methylated KCNQ5 for all stage CRC detection, 85.9 and 77.3% respectively, fell within the range of other markers from 71.2% for methylated HPP1 (55) to 92.5% for methylated COL4A2 (33).…”
Section: Discussionsupporting
confidence: 76%
“…A direct comparison study found significantly higher m SEPT9 level in stool samples than in plasma. Whereas the performance of both tests in detecting all stage CRC was similar, stool m SEPT9 test achieved improvement of 35.9% and 7.9% in sensitivity for detecting AA and stage I-II CRC when compared to plasma test ( 31 ). Jensen et al identified three methylation markers, C9orf50 , KCNQ5 , and CLIP4 , and evaluated their performance for CRC detection with plasma samples.…”
Section: Discussionmentioning
confidence: 87%
“…We examined the last five years’ literature for methylated genes currently targeted by FDA or NMPA screening kits: mSDC2, mSEPT9, mNDRG4, and mBMP3. With our specific filters, we found six studies dedicated to mSDC2 [ 33 , 34 , 35 , 36 , 37 , 38 ] and seven studies for mSEPT9 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]; two described mBMP3 performance [ 46 , 47 ], while no study evaluated mNDRG4 alone. A multi-target approach evaluating these biomarkers and others was employed in 16 studies, 5 of them deciphering mSDC2 and mSEPT9 performance [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…CpG island hypermethylation of the SEPT9 promoter leads to altered expression—eliminating its tumor suppressor activity, which contributes to carcinogenesis [ 54 ]. mSEPT9 was evaluated in four studies as a single biomarker [ 39 , 40 , 42 , 45 ]. Three studies compared mSEPT9 performance with other known screening tools [ 41 , 43 , 44 ] ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%